Regulation and entry into telecommunications markets - Bijl, Paul de, 1967- (Cambridge University Press, 2002)
This book examines competition and regulation in the liberalized telecommunications markets. The authors analyse a broad range of market constellations, in particular the hot topic of access price regulation in asymmetric markets, and derive from this various policy recommendations. It is a valuable resource for academics, regulators and telecommunications professionals.